The Influence of Islamic Educational Games on Students’ Discipline Character - Alimni; Siregar, Amri; Amin, Alfauzan (GHAITSA : Islamic Education Journal, 2026)
The purpose of this study is to determine the influence of Islamic educational games on students’ discipline character at SMPIT Al Marjan Bengkulu City. This study aims to identify how effectively Islamic educational games can shape and improve students’ disciplinary behavior in the learning process. This study employed an associative research method with both quantitative and qualitative approaches. Data were collected using questionnaires and interviews. Statistical analysis was performed using IBM SPSS version 26, including validity, reliability, linear regression, and hypothesis testing. Instruments used were Likert-scale questionnaires and structured interview guides with 50 student participants. The results indicate that Islamic educational games significantly influence students’ discipline character, with a significance value of 0.001 < 0.05 and a t-value of 3.654 > 0.279. The coefficient of determination (R² = 0.218) shows that 21.8% of the variation in students’ discipline character is explained by the use of Islamic educational games. Qualitative findings suggest inconsistent student engagement, limited motivation, and moderate perceived benefits toward improving discipline and learning responsibility. This study introduces an integrated analysis combining quantitative regression and qualitative interviews to evaluate the impact of Islamic educational games on students’ discipline character. It provides new insights into how faith-based digital media can serve as an alternative educational tool to foster behavioral discipline, enriching existing character education research from an Islamic pedagogical perspective.